Роль креативного менеджменту у формуванні творчого потенціалу підприємства - Бортнікова, М. Г.; Крохмальна, Я. О.; Bortnikova, M. H.; Krokhmalna, Ya. O. (Видавництво Львівської політехніки, 2022)
Проаналізовано підходи до визначення терміна «креативний менеджмент». Розглянуто концепцію креативного класу, в якому новими рушійними силами економічного розвитку є «суперкреативне ядро» (ураховуючи художників, дизайнерів) і «творчі професіонали» (серед яких менеджери, юристи). Виокремлено основні ознаки креативності персоналу підприємств. Охарактеризовано напрями креативного менеджменту в сфері маркетингу, зокрема: маркетингові комунікації, реклама, бренд-менеджмент, медіа-менеджмент. Запропоновано етапи розроблення креативних рішень на підприємстві. Досліджено основні завдання креативного менеджменту підприємств та наведено переваги сприяння творчості на робочому місці.

Modern business trends create new requirements for the use of innovative tools for searching and generating ideas in order to increase the efficiency of enterprises. It is creativity that contributes to the personal and professional self-development and self-improvement of the company’s employees. Analyzing the research of recent years in the field of management, it can be emphasized that in order to achieve important organizational results, such as innovation, growth and management success, it is creativity that is important. Key industries in the creative economy include: advertising, architecture, arts and crafts, design, fashion, film, video, photography, music, performing arts, publishing, research and development, software, computer games, electronic publishing, television and radio. The era of informational and intellectual development became the era of the XXI century, which was marked by the transition from rationality to creativity. The concept of the “creative class” offers a new way of understanding the mechanisms of wealth creation. In the period of the “post-industrial” economy, the new driving forces of economic development are the “super creative core” (including artists, designers) and “creative professionals” (including managers, lawyers). Organizational management is complex and multidimensional in nature. It combines a number of elements, activities and processes aimed at achieving the organization’s goals. Amidst a rapidly changing business landscape, organizations are moving forward from the classic criteria of cost and performance to integrating creativity and innovation for overall efficiency. Such integration involves the study and implementation of concepts at different functional levels of management for the development of the creative potential of enterprises. Development of creative solutions at the enterprise involves market research and analysis, generation of new ideas, evaluation of alternatives and implementation of innovative solutions. Creative management is what is needed in the 21st century in order for the business to stay afloat and maintain its competitive advantage. The main skill that managers are looking for in skilled workers today is creativity. Creativity management ensures the development of an individual's creative skills, his ability to generate fundamentally new ideas and bring them to a concrete result. That is why the achievement of the goals and objectives of creative management requires improvement of the tools for the development and implementation of innovative solutions.
The role of creative management in forming the creative potential of the enterprise
Keywords: креативний менеджмент; креативний клас; творчий потенціал; креативність; креативна ідея; інновація; creative management; creative class; creative solutions; creativity; creative solutions; innovation; 658; 005.95